Association between acute respiratory acidosis and hyperkalemia during esophageal cancer surgery in the prone position: A multicenter retrospective observational study protocol - Sakura Okamoto; Tokiko Tochii; Jyunya Nakada; Hideaki Note (PLoS ONE, 2026)
Introduction Esophagectomy in the prone position can induce acute respiratory acidosis. While it is known that metabolic acidosis can significantly elevate serum potassium, the effect of respiratory acidosis is conventionally considered to cause minimal or no elevation. However, clinical practice in this surgical setting sometimes reveals a greater-than-expected degree of hyperkalemia. The objective of this study is to investigate the association between this acute respiratory acidosis and hyperkalemia, and to explore its clinical implications. Methods and analysis This is a retrospective, two-center observational study of adult patients who underwent thoracoscopic esophagectomy in the prone position at two major Japanese institutions between January 2022 and December 2024. The primary outcome is the mean difference in serum potassium levels between the supine (baseline) and prone-position phases, analyzed as a paired-design within each patient. Key secondary outcomes include: 1) a multivariable analysis to identify factors associated with the magnitude of potassium increase; 2) a sensitivity analysis of the primary outcome after excluding cases with significant metabolic acidosis (e.g., base excess < −5 mmol/L); and 3) correlation analyses between the change in potassium and various physiological parameters, including PaCO₂ and markers of metabolic stress. Analyses will include the paired t-test, correlation analyses, and multivariable regression models.